The Study of project risk management implementation critical success factors and construction project success: A correlation Study - SHAWISH, WALEED ABDULKARIM (2018)
Itswell known and popular that construction projects are highly complex and vulnerable to risks exposure that results in project success objectives variations and overruns if not managed effectively. Thus, project risk management addressed as one of the main components of PMBOK and knowledge in project management practices. The number of researches conducted in construction project risk management where focused on the implementation project risk management processes, identifying critical success factors of project risk management and different enterprise risk management frameworks to minimize the impacts of negative events possibility and its consequences of risks encountered in construction projects and enhance project success. However, a gap between construction project risk management in theory and actual practice of risk management identified in UAE construction projects. In addition, the understanding of critical success factors of Enterprise risk management ability to be utilized in project risk management to ensure success in construction projects. This study adopted mixed method, both qualitative and quantitative methods to bridge the gap between theory and actual practices of risk management. The study divided into two phases. The first part of the study is to rank the importance of Enterprise risk management critical success factors for project risk management implementation and the second part is to correlate the project risk management implementation to construction project success. The qualitative method conducted through reviewing extensively the academic literature reviews as the primary sources and conducting surveys and questionnaires as secondary sources. The quantitative method was conducting analysis through using SPSS software for the data collected from secondary sources to validate research questions and hypothesis. Furthermore the, results of the study presented the vagueness in determining the relationship between most important critical success factors and project risk management in addition to determining an exact definition of construction project success.